The Lockdown Effect on the Profitability Position of Tata Steels Ltd India - R V Harisha Kumar; Dr. John Benedict (International Journal of Engineering and Management Research, 2022)
Tata steels in second largest steel industry in India followed by SAIL. This study is to analyze impact of pandemic in Tata steels ltd. The scope of this study is to find the profitability and solvency position of Tata steels ltd, in the period from 2016-17 to 2020-21. The company faced a little impact of the pandemic in some aspects. The company’s debt is higher than the equity of the company. The overall liquidity and the cash circulation in the company is to be increased to run the company in an uninterrupted manner.